THREE APPROACHES OF WORD MEANING OF THE FIGURATIVE LANGUAGES TRANSLATION - Tri Sutrisna Agustia (AT-TA'LIM, 2012)
Figurative language is widely used in any form of communication particularly in daily communication such as articles in newspaper, advertisements, novels, poems and so forth. However, this study is limited to the analysis of the figurative languages with reference to the translation of the novel The Other Side Of Me into Sisi Lain Diriku. This study is aimed at finding out the type of the Figurative Languages that found in the novel and finding the equivalence if the text meaning based on 3 Word-Meaning Approaches theory combined with Knowledge Based Theory. The analysis was presented in the forms of words and sentences.Â  The result of this study showed that there are 4 types of Figurative Languages. And there also shown the relation between 3 meaning approaches and knowledge based theory.